Urgensi Mata Kuliah Filsafat Agama dalam Membangun Karakter Bangsa yang Beradab - Husna Amin (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2011)
More than two centuries, Islam accoutered with attack of civilizations andperceptions of the other world, which threatened every teaching of the religion.The attack has corrupted many parts of Islamic civilization, which were built overthe centuries. For the centuries, Islam established his political independencealmost in whole part of the world. The modern West domination over religion,philosophy, culture, art, politics, social life and others has continued penetrating the depth and width of Dar al-Islam, which has threatened not only traditional institutions of Muslim community but also Islam as a religion. Guidance and solution to overcome these problems become more difficult not only caused by the complexity and chaos of modernity but is also contributed by majority Muslim who ignore the teaching of their faith. Pragmatic-empiric lifestyle deeply brings human to forget the existential dimension of self as creation that are responsible to himself and God. It is that led to destruction of human civilization. So that it is urgent for clergies to put forward their motivation and consciousness to be universal law (moral) to gauge their activities. The nation’s characters that is supposedly in the frame of universal law as determinant of one civilization now shift to and is replaced by earthly positive-empiric law, which led a state to the destruction and the abjection. This article offers the philosophy of religion as an alternative to overcome the nation problems. Through practicing rationalphilosophical thinking (philosophy) and mystic - spiritual (religion) methods evenly in the perspective of philosophy of religion, the writer attempts to analyses the nation problem and provide alternative thoughts to save the civilization.